Community actions to revitalize urban blue and green capitals: learnings from Abberley Park, Ōtautahi Christchurch, Aotearoa, New Zealand - Maria Rita D. J. Dionisio; Mirjam Schindler; Edward Challies; Tyler McNabb; Amanda Yates (Ecology and Society, 2025)
This study aims to investigate the revitalization of blue-green capital in urban communities, to enhance local well-being and social-ecological resilience at the neighborhood scale. Fostering more-than-human well-being can play a central role in maintaining overall health in cities. The study first investigates what are the key priorities recognized to enhance blue-green capital. Second, what are key challenges and opportunities for community-led revitalization of blue-green capital? And how can local communities act to bridge identified gaps in revitalization processes centered on blue-green capital? We partnered with the St. Albans Resident Association (SARA), to orient a place-based, context-sensitive approach to the methodology to address the research questions in the Abberley Park, in Ōtautahi Christchurch, New Zealand case study. This is one of eight city heritage parks in Christchurch and an example of a lush mix of native and introduced, exotic trees and vegetation. However, the health of the St. Albans Stream, as seen in the park, is a concern for the local community. Nature-based solutions to control pests and invasive species, and riparian planting can encourage local actors to align short-term goals and active efforts toward revitalizing the St. Albans Stream, starting with the identified areas at the park. The results highlight the perspectives of long-term residents, volunteers, and community leaders, which can inform local policies and actions focused on enhancing the health of the St. Albans Stream and its sensitive habitats starting at Abberley Park. Enabling the identification of key local actors in the St. Albans community, the research demonstrates the importance of context-sensitive approaches to identify potential organizational and social contributions when considering blue-green capital and urban well-being at neighborhood scales.